2021
DOI: 10.1002/adfm.202102840
|View full text |Cite
|
Sign up to set email alerts
|

Quasi‐Ordered Nanoforests with Hybrid Plasmon Resonances for Broadband Absorption and Photodetection

Abstract: With the continuing development of green energy technology, solar energy is the most widely distributed and easily utilized form of energy in nature. Highabsorption absorbers over a wide spectrum range are beneficial for solar energy harvest. Herein, a fast and efficient method is developed to fabricate a broadband absorber consisting of quasi-ordered nanoforests and metal nanoparticles using a simple plasma bombardment process on a 4-inch silicon wafer, offering high throughputs that can meet practical applic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 63 publications
0
18
0
Order By: Relevance
“…Li et al designed Ag-quasiordered nanoforests (Ag-QNF) through a fast and efficient method by plasma bombardment on a silane coupling agent (SCA)-added polyimide (PI). 75 The Ag-QNF exhibits an average absorption higher than 90% from 300 nm to 2500 nm (Figure 3g), which was ascribed to the hybrid LSPR effect and the cavity mode resonances in the Ag-QNF, as well as the light trapping effect of the QNF (Figure 3h). Note that the broad absorption of Ag-QNF is independent of the polarization and the incident angle of light.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Li et al designed Ag-quasiordered nanoforests (Ag-QNF) through a fast and efficient method by plasma bombardment on a silane coupling agent (SCA)-added polyimide (PI). 75 The Ag-QNF exhibits an average absorption higher than 90% from 300 nm to 2500 nm (Figure 3g), which was ascribed to the hybrid LSPR effect and the cavity mode resonances in the Ag-QNF, as well as the light trapping effect of the QNF (Figure 3h). Note that the broad absorption of Ag-QNF is independent of the polarization and the incident angle of light.…”
Section: Methodsmentioning
confidence: 99%
“…(h) Schematic illustration of the plasmon-enhanced light absorption within the Ag-QNF structures. [Panels (g) and (h) were reproduced with permission from ref . Copyright 2021, Wiley–VCH Verlag GmbH & Co. KGaA, Weinheim, Germany.…”
Section: Diversified Metal Nanostructuresmentioning
confidence: 99%
See 1 more Smart Citation
“…[11] At present, the commonly used solar-thermal conversion materials include carbon-based materials, [12][13][14][15] organic polymers, [16,17] inorganic semiconductors, [18][19][20] and metal nanoparticles. [21,22] Among these materials, reduced graphene oxide (RGO) is well suitable for solar-thermal energy conversion because of its outstanding solar light absorption, high specific surface area, and excellent thermal stability. [23] Huo et al [24] reported a nitrogendoped graphene/carbon hybrid aerogel for efficient solar steam generation, exhibiting excellent hydrophilicity for water supply and abundant micro-pores for vapor escape, achieving a water evaporation rate of 1.558 kg m −2 h −1 and confirming the significant potential of RGO in the area of photothermal conversion.…”
Section: Reduced Graphene Oxide Decorated Cellulose Acetate Filter Ev...mentioning
confidence: 99%
“…Broadband light absorbers are highly desirable in various applications including photodetection, , photothermic conversion , and solar energy harvesting . There have been many reports on broadband light absorbers from the visible-to-IR wavelength range by various methods .…”
Section: Introductionmentioning
confidence: 99%